OP R DI - Set for modeling depths of riverbeds and basins of stagnant water [Tender documents : T26734499] (MENA Report, 2015)
The subject of procurement is the delivery suite for modeling depths of riverbeds and basins of stagnant waters further specified in the tender documents, which is part of the instrumentation project paid from the op r & di. set is applicable to the device sontek riversurveyor m9, which is used for measuring the flow at high water levels. this consists of a software sensor and to compensate for temperature and density stratification running or standing water. the set also includes the provision of activities consisting in...